Making a difference: Language teaching for intercultural and international dialogue - Byram, Michael; Wagner, Manuela (Foreign language annals, 2018)
Language teaching has long been associated with teaching in a country or countries where a target language is spoken, but this approach is inadequate. In the contemporary world, language teaching has a responsibility to prepare learners for interaction with people of other cultural backgrounds, teaching them skills and attitudes as well as knowledge. This article presents the main concepts involved in this view of language teaching: the notion of culture, the language‐culture nexus, and intercultural competence. It also explains the implications of the approach in terms of the skills, attitudes, and knowledge that should be taught. The article goes further: It argues that language teaching needs to be linked to other disciplines in order to develop an approach that integrates insights from citizenship education. All of this has implications for teachers’ professional identity and for cooperation across the curriculum. The Challenge Linguistic competence needs to be enriched with deep intercultural competence. How can world language educators help language learners to develop increasingly sophisticated linguistic and intercultural knowledge and skills and apply them in other courses and experiences so as to enact their intercultural citizenship in the here and now? Video & Discussion